Interleukin-4 Receptor Alpha Expressing B Cells Are Essential to Down-Modulate Host Granulomatous Inflammation During Schistosomasis - Ndlovu, Hlumani; Nono, Justin Komguep; Abdel Aziz, Nada; Nieuwenhuizen, Natalie Eva; Brombacher, Frank (Frontiers in Immunology, 2018)
Schistosomiasis (bilharzia) is a parasitic helminth disease that can cause severe inflammatory pathology leading to organ damage in humans. Failure of the host to regulate egg-driven granulomatous inflammation causes host morbidity during chronic infection with Schistosoma mansoni. Although the importance of B cells in regulating pathology during chronic infection has been well defined, the specific contribution of IL-4Rα-expressing B cells is still unknown. To address this, we examined B cell-specific IL-4Rα-deficient (mb1creIL-4Rα-/lox) mice in three experimental models of schistosomiasis: high-dose (100 cercariae), low dose (30 cercariae) and a synchronous egg challenge. In the high dose model, we found that mice deficient in IL-4Rα-expressing B cells were more susceptible to acute schistosomiasis than B cell-deficient (μMT) mice, succumbing to infection at the acute stage whereas μMT mice survived until the chronic stage. An S. mansoni egg challenge model demonstrated that deleting IL-4Rα expression specifically on B cells resulted in increased lung granulomatous pathology, suggesting a role for this B cell subset in controlling granulomatous pathology. In agreement with this, a low dose model of schistosomiasis – which mimics the course of clinical chronic disease - demonstrated that depleting IL-4Rα-expressing B cells in mb1creIL-4Rα-/lox mice considerably impaired the host ability to down-modulate granulomatous inflammation in the liver and gut during chronic schistosomiasis. Taken together, our findings indicate that within the B cell compartment, IL-4Rα-expressing B cells in particular down-modulate the deleterious egg-driven tissue granulomatous inflammation to enable host survival during schistosomiasis in mice.